Embryonic and foetal Islet-1 positive cells in human hearts are also positive to c-Kit - C. Serradifalco; P. Catanese; L. Rizzuto; F. Cappello; R. Puleio; V. Barresi; C. M. Nunnari; G. Zummo; V. Di Felice (European Journal of Histochemistry, 2011)
During embryogenesis, the mammalian heart develops from a primitive heart tube originating from two bilateral primary heart fields located in the lateral plate mesoderm. Cells belongings to the pre-cardiac mesoderm will differentiate into early cardiac progenitors, which express early transcription factors which are also common to the Isl-1 positive cardiac progenitor cells isolated from the developing pharyngeal mesoderm and the foetal and post-natal mice hearts. A second population of cardiac progenitor cells positive to c-Kit has been abundantly isolated from adult hearts. Until now, these two populations have been considered two different sets of progenitor cells present in the heart in different stages of an individual life. In the present study we collected embryonic, foetal and infant hearts, and we tested the hypotheses that c-Kit positive cells, usually isolated from the adult heart, are also present in the intra-uterine life and persist in the adult heart after birth, and that foetal Isl-1 positive cells are also positive to c-Kit. Using immunohistochemistry we studied the temporal distribution of Isl-1 positive and c-Kit/CD105 double positive cells, and by immunofluorescence and confocal analysis we studied the co-localization of c-Kit and Isl-1 positive cells. The results indicated that cardiomyocytes and interstitial cells were positive for c-Kit from the 9th to the 19th gestational week, that cells positive for both c-Kit and CD105 appeared in the interstitium at the 17th gestational week and persisted in the postnatal age, and that the Isl-1 positive cells were a subset of the c-Kit positive population.